On the binary nature of SS 433 - Schmidtobreick, L; Blundell, K (2006)
We present time-resolved optical spectroscopy of the famous X-ray binary SS 433. We obtained 61 medium resolution spectra spread over three months and thus cover roughly five orbits and about half a precession phase. We used various emission lines, that we attribute to the accretion disc, to determine the radial velocities of the compact component. They are of course modulated with the orbital period but in addition show a variation of the system velocity on a longer time scale. With the present data it is not possible to determine whether this is a transient effect or a periodic variation, although we present various possible interpretations of this effect. © Springer Science+Business Media B.V. 2006.